NAVIGATING THE PSYCHOLOGICAL CHALLENGES OF TEENAGERS LEARNING A FOREIGN LANGUAGE - Ibragimova Dilafruz Shukhratovna; Meliboyeva Nazokatxon Elyor kizi (TADQIQOTLAR.UZ, 2023)
Abstract: Learning a foreign language can be a challenging experience, particularly for adolescents. Apart from the linguistic difficulties encountered, they also face emotional and psychological challenges. This article identifies the psychological challenges teenagers encounter when learning a foreign language and suggests strategies to help them overcome these challenges. It explores the impact of self-esteem, motivation, anxiety, and identity on the learning process and offers practical recommendations for promoting a positive language learning experience for teenagers.